Digital Literacy for Hizbul Wathan Scout Movement Cadres in Batu City - Yufis Azhar; Mahar Faiqurahman; Wildan Suharso (Universitas Muhammadiyah Malang, 2021)
Related to human resource development, Indonesia will take the advantage of demographics bonus in 2030-2040, which is the productive age of the Indonesian population is greater than the non productive age. Certainly, this becomes a challenge for Indonesian people to develop the human resources who are ready to face 4.0 Industry era, so that the good insight and abilities in digital literacy, which is the basic knowledge of the 4.0 Industry, are needed for young generation today. This is crucial considering the development of Information and Communication Technology (ICT) is very vulnerable to be misused, so it will not give benefit to the country. Hizbul Wathan (HW), one of the scouting organization, which develop the young generation, expected to play an active role in the development of 4.0 Industry era, so that the knowledge and skill in the field of ICT is absolutely needed. By this community service activity, we have given insight and deep knowledge about digital literacy to the Hisbul Wathan Scouting Organization, especially for Regional Quarters of Batu City members.